INVENTARISASI JAMUR DI TAMAN HUTAN RAYA (TAHURA) BERASTAGI KABUPATEN KARO, SUMATERA UTARA - RAHMADINA RAHMADINA (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2021)
This study aims to determine the types of mushrooms, mushroom identification methods, the benefits of mushrooms, and how to collect mushrooms which was carried out from August to November 2019 at the Berastagi Forest Park (TAHURA), Karo Regency, North Sumatra. The sampling site was taken towards the North where the typography of the field is partly flat, steep and hilly with an air temperature of 23Â°C. Geographically, this Forest Park is located at 001'16"-019"32 North Latitude and 9812'16"- 9841'00" East Longitude. The method used is the Cruise Method or the method of cruising as far as 1 Km. Based on the results of research that has been carried out, it was found that 5 macroscopic mushroom families were Pythiaceae, Marasmiaceae, Ganodermataceae, Coprinaceae, Polyporaceae and 11 species of macroscopic fungi namely, Pythya vulgaris, Trametes versicolor, Ganoderma sp1, Ganoderma sp2, Ganoderma sp3, Marasmius siccus, Coprinus sp1, Coprinus sp2, Coprinus sp3, Laetiporus sp. The benefits of mushrooms in Trametes versicolor can be used for the treatment of HIV. Marasmius siccus is an edible mushroom species. Coprinus sp, a type of fungus used as an antioxidant and 6 species of macroscopic fungi that are toxic (poisonous), namely Pythya vulgaris, Ganoderma sp1, Ganoderma sp2, Ganoderma sp3, Laetiporus sp. Macroscopic mushrooms were collected by cutting the base of the fruit stem.Â Keywords: Inventory, Mushrooms, Berastagi Forest Park.